2008
DOI: 10.1086/588277
|View full text |Cite
|
Sign up to set email alerts
|

Drift Effects and the Cosmic Ray Density Gradient in a Solar Rotation Period: First Observation with the Global Muon Detector Network (GMDN)

Abstract: We present for the first time hourly variations of the spatial density gradient of 50 GeV cosmic rays within a sample solar rotation period in 2006. By inversely solving the transport equation, including diffusion, we deduce the gradient from the anisotropy that is derived from the observation made by the Global Muon Detector Network (GMDN). The anisotropy obtained by applying a new analysis method to the GMDN data is precise and free from atmospheric temperature

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 25 publications
7
59
0
Order By: Relevance
“…It has been used for studying the directional anisotropy of high-energy cosmic ray intensity which often shows a dynamic variation when an interplanetary coronal mass ejection (ICME) accompanied by a strong shock approaches and arrives at the Earth (Okazaki et al 2008). It also has been used for studying the physical aspects of these interplanetary structures (Munakata et al 2005;Kuwabara et al 2009).…”
Section: The Global Muon Detector Network (Gmdn)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used for studying the directional anisotropy of high-energy cosmic ray intensity which often shows a dynamic variation when an interplanetary coronal mass ejection (ICME) accompanied by a strong shock approaches and arrives at the Earth (Okazaki et al 2008). It also has been used for studying the physical aspects of these interplanetary structures (Munakata et al 2005;Kuwabara et al 2009).…”
Section: The Global Muon Detector Network (Gmdn)mentioning
confidence: 99%
“…There are many methods of analyzing and removing the temperature effect from cosmic ray intensity observed by ground muon detectors. The simplest methods consist of the comparison of the cosmic ray intensity with: surface temperature changes, the variation of the altitude of maximum muon production (MMP), or the temperature variation at this altitude (Blackett 1938;Hess 1940;Duperier 1949;Trefall 1955a;French & Chasson 1959;Okazaki et al 2008;De Mendonça et al 2013). There are also methods that consider the temperature variation along the entire atmosphere through empirical or theoretical analyses (Sagisaka 1986;Dorman 2004;Berkova et al 2011;De Mendonça et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We calculate the daily mean ξ GEO(GG) z in T and A sectors from hourly data in the same manner as described in the section 2.1 for the GMDN data analysis. Okazaki et al (2008) [2] showed that the day-to-day variation of ξ GEO(GG) z followed well the variation of ξ GEO is partly due to the statistical error of the GG-component in equation (2.2), but it is also due to the contribution from the equatorial anisotropy contained in the GG-component. Figure 1 shows the average ξ GEO(GG) z in every month.…”
Section: Pos(icrc2015)056mentioning
confidence: 80%
“…Based on observations of the NSA which varies depending on the orientation of the Interplanetary Magnetic Field (IMF) around the Earth, it has been demonstrated that the GG-component can be used for deriving reliable sector polarity of the IMF which is defined as away (toward) when the IMF directs away from (toward) the Sun [11]. It is also reported that the NSA deduced from the GG-component is consistent with the anisotropy observed with the GMDN [2,12].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation